PERBANDINGAN HASIL BELAJAR IPA SISWA ANTARA MODEL PEMBELAJARAN BERBASIS MASALAH DENGAN MODEL PEMBELAJARAN INKUIRI TERBIMBING - Merta Herza; Abdurrahman -; Viyanti - (Jurnal Pembelajaran Fisika, 2012)
The objective of this research is to find out the comparison of students’ natural science learning results in heat material using problem based learning and inquiry based learning, and to find out the highest learning results amongst problem based learning and inquiry based learning.This is a quasi experiment research with one-group pretest-post test design. Samples were 61 students in grade VII of classroom VIIA and VIIB in State Junior High School 22 in Bandar Lampung. Samples were taken using purposive sampling technique. Data were obtained from learning results of student’s post test. Data were analyzed using data normality test, estimating score N-gain, and dependent sample t-test.The results conclude that there is an improvement of average of students’ learning results by using problem based learning and inquiry based learning. The students learning results in problem based learning is higher than in inquiry based learning. The abilities of students having problem based learning are better than those who have inquiry based learning.Key words: Learning model problem based learning and guided inquiry